Examining Technology Integration in Micro Teaching: Unique Insights from Pre-Service Teachers at Universitas Widya Gama Mahakam Samarinda Using the Harris, Grandgenett, and Hofer Framework - Sukaena; Limbong, Effendi; Rusmawaty, Desy (Borneo Educational Journal (Borju), 2024)
The objective of the study was to know the categories of Harris J., Grandgenett, N., and Hofer M toward preservice teachers in Micro Teaching Course at Widya Gama Mahakam Samarinda University. This study was conducted at fifth semester of English Education Department, University of Widya Gama Mahakam Samarinda. This study focused on technology integration of pre service teachers that implemented in micro teaching course. Design of this study was qualitative study. There were 24 pre-service teachers in this study determined by purposive sampling. The instrument used was interview guide by Harris J., Grandgenett, N., and Hofer M. There were 5 pre-service teachers who were willing to be the interviewees. Then, the researcher collected the data by simulated recall interview and video as the source of data. The result of the study showed pre service teachers were good enough in implementing technology integration in their micro teaching course. There were four categories seemed in this study. They were about curriculum goals, instructional strategy, technology selection, and fit. Researchers conclude that all the categories were fit together in a harmony although some of preservice teachers still using low technology in their practice